Proliferation is necessary for both repair and mutation in transgenic mouse cells - Bielas, Jason H. (The National Academy of Sciences, 2000)
Proliferating cells are often presumed to be more mutable than quiescent cells because they have less time to repair DNA damage before DNA replication. Direct tests of this hypothesis have been confounded by the need for cell division before a mutation can be detected. We have avoided this problem by showing that the Big Blue mouse cell line permits the dynamic quantification of both lesions and mutations in the complete absence of cell division. These cells carry the bacterial lacI gene in a λ shuttle vector. Mutant plaques recovered by in vitro packaging of the mouse DNA can arise from mutations sustained either in mouse cells or in the bacteria. The proportion of mutant phage contained within a mutant plaque can distinguish these two types of mutation. Mutations formed in mouse cells yield >90% mutant phage because both DNA strands are mutant. On the other hand, mutations formed in the bacteria from adducted DNA yield ≤50% mutant phage, because one of the DNA strands is wild type. Immediately after exposure to a test mutagen, ethylnitrosourea, all induced mutations were formed in the bacteria, but after approximately one cell division, the reverse was true and all mutations arose in the mouse cells. Only one-fifth as many mutations were recovered from quiescent cells and all arose in the bacteria, showing that the mouse cells made no mutations in the absence of proliferation. Surprisingly, the mouse cells did not repair any of the premutagenic damage during 4 days of quiescence. When these quiescent cells were induced to proliferate, however, both repair and mutation fixation ensued.